Cohesive DS-PID and FQL Control Mechanisms to Enhance the Performance of the Electric Vehicle System - Siva Subramanian, A. P.; Sutha, B. S.; Aravind Britto, K. R. (Elektronika ir Elektrotechnika, 2022)
Electric Vehicles (EVs) have become more popular and attractive in recent days, due to their benefits of zero carbon emissions, cost effectiveness, reduced maintenance, and effectiveness. In which, controlling the speed of motor and proper power regulation are the important tasks for designing the EV systems. For this purpose, various control techniques have been developed in the existing works, but it limits with the major problems of reduced efficiency, increased error output, and high time consumption. To solve these problems, this paper intends to develop an advanced and novel optimization-based control algorithms for controlling the speed of motor and regulating the output power of EV systems. Here, the Maximum Peak Point Control (MPPT) technique is utilized to extract the increased amount of power from the PV panels. Then, the Dual Fold Luo (DFLuo) DC-DC converter topology is utilized to regulate the output DC power to improve the battery storage of the EV system. Consequently, the optimization-based Dynamic Supervision-PID (DS-PID) control mechanism is employed to recognize the maximum power from PV to generate the control pulses for switching activities. After that, the Fractional Quadratic Linearizer (FQL) control technique is utilized for controlling the speed of BLDC motor, in which the current limiter controls the speed based on the input features of the brake and the speed of motor running at each time instant. During the simulation evaluation, the results of the proposed control mechanisms are validated and compared using various performance measures.